Where Is Conflict Mediation Used? A 20-Year Period Systematic Literature Review - Bonamigo Gaspodini, Icaro; da Rosa Alves, Alessandro; Freitas de Oliveira, Luiz Ronaldo (Revista de Psicologia da IMED, 2016)
Mediation is widely considered an effective means of conflict resolution. Although some studies mention social environments where this practice takes place, they do so in an introductory or general manner. The objective of this study is to categorize social environments where conflict mediation is used and provide examples of conflicts that are tackled through mediation. A systematic literature review was designed to examine 207 articles published in scientific journals, for a 20-year period (1994-2014). Results showed five social environments (family, educational/academic, work/professional, community/national, and international contexts) and 45 subcategories of themes related to each context. The wide use of conflict mediation and its importance were discussed in the light of the Ecological Systems Theory.